2021
DOI: 10.21037/atm-20-8103
|View full text |Cite
|
Sign up to set email alerts
|

In vivo endothelialization and neointimal hyperplasia assessment after rabbit carotid endarterectomy with bovine pericardium

Abstract: Background: Previous studies have reported that the use of a patch in carotid endarterectomy (CEA) surgery can reduce the rate of restenosis and perioperative complications. The goal of this study was to compare the short-and medium-term outcomes of endothelialization and neointimal hyperplasia of patch closure (PC) angioplasty in CEA with direct closure (DC) in a rabbit model. A bovine pericardial patch (BPP) was used in the PC procedures.Methods: Two carotid arteries were dried by air flow to simulate endart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…8 Whilst animal studies have demonstrated endothelialisation of BP grafts used for arterial reconstruction, there is a paucity of data relating to endothelialisation of these grafts when used for IVC reconstruction in humans. 9,10 Here we show evidence that BP grafts used for IVC reconstruction demonstrate endothelialisation, however, further larger scale studies are needed to further characterise this finding.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…8 Whilst animal studies have demonstrated endothelialisation of BP grafts used for arterial reconstruction, there is a paucity of data relating to endothelialisation of these grafts when used for IVC reconstruction in humans. 9,10 Here we show evidence that BP grafts used for IVC reconstruction demonstrate endothelialisation, however, further larger scale studies are needed to further characterise this finding.…”
Section: Discussionmentioning
confidence: 70%
“…8 Whilst animal studies have demonstrated endothelialisation of BP grafts used for arterial reconstruction, there is a paucity of data relating to endothelialisation of these grafts when used for IVC reconstruction in humans. 9,10 Here we show evidence that BP grafts used for IVC reconstruction demonstrate endothelialisation, however, further larger scale studies are needed to further characterise this finding.
Image 2.Macroscopic view of the liposarcoma encasing the IVC from case 1.
Image 3.Macroscopic view of the IVC (arrow) and retroperitoneal tissue from case 2.
Image 4.Low power view of graft showing lumen (arrow), endothelialisation, and underlying scar with foreign body reaction (left). High power view of graft showing evidence of endothelialisation (arrow head) (right).
…”
Section: Discussionmentioning
confidence: 99%